2005
DOI: 10.1158/1535-7163.mct-05-0011
|View full text |Cite
|
Sign up to set email alerts
|

Role of p21waf1/cip1 in effects of oxaliplatin in colorectal cancer cells

Abstract: Clinical studies have shown that oxaliplatin, a novel platinum derivative, is a potent chemotherapeutic agent for colorectal cancer when combined with 5-fluorouracil and leucovorin. Although the toxic activity is based on covalent adducts between platinum and DNA, its actual biological behavior is mostly unknown. In an effort to explore the mechanism of tumor susceptibility to oxaliplatin, we examined the cytotoxic effects of oxaliplatin in colorectal cancer cell lines in reference to p53 gene status. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
7
27
0
Order By: Relevance
“…A total of 50.6% of HCT-8 cells incubated with O + F/fiber were arrested at the G0/G1 phase relative to 54.4% of free drugs at 24 h postincubation, whereas only 44.97% and 44.29% of cells in empty PLLA fiber group and control group were arrested at the G0/G1 phase (p50.05). The above results were in agreement with the previous studies (Hata et al, 2005), which showed that in a p53-dependent pathway, oxaliplatin enhanced the expression of p21waf1/cip1 protein, which may be responsible for the growth-inhibitory activity by delaying the transition from G0/G1 to S phase in HCT-116 human colorectal cells.…”
Section: Cell Cycle Analysissupporting
confidence: 93%
“…A total of 50.6% of HCT-8 cells incubated with O + F/fiber were arrested at the G0/G1 phase relative to 54.4% of free drugs at 24 h postincubation, whereas only 44.97% and 44.29% of cells in empty PLLA fiber group and control group were arrested at the G0/G1 phase (p50.05). The above results were in agreement with the previous studies (Hata et al, 2005), which showed that in a p53-dependent pathway, oxaliplatin enhanced the expression of p21waf1/cip1 protein, which may be responsible for the growth-inhibitory activity by delaying the transition from G0/G1 to S phase in HCT-116 human colorectal cells.…”
Section: Cell Cycle Analysissupporting
confidence: 93%
“…HCT-116 p53 -/-and HCT-116 p21 -/-cells lost both the growth-inhibitory effect and G 0 /G 1 arrest pattern of the cell cycle after DPD treatment. Previous studies have also shown the p21 induction and G 1 arrest by a p53-independent pathway (22) and the p21 involvement in cell growth and cell cycle of HCT-116 cells (23)(24)(25). It has been suggested that DPD induces p21 expression through a p53-independent pathway in colon cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Oxaliplatin and curcumin are known to cause G2/M cell cycle arrest in some cell lines, [16][17][18] which may account for the decrease in proliferative capacity following treatments with these agents, both singly and combined in the 2 colon tumor cell lines.…”
Section: Effect Of Oxaliplatin and Curcumin On Cell Cycle Distributionmentioning
confidence: 99%